A Product Space Perspective on Structural Change in Morocco - Osorio Rodarte, Israel; Lofgren, Hans (World Bank, Washington, DC, 2015)
Drawing on international trade data, this paper uses the product space approach to analyze changes in Morocco’s goods exports in 1990–2010 and future export priorities. The level of Morocco’s gross domestic product and its moderate growth match the predictions of product space analysis, informed by changes in the income potential of Morocco’s export basket, reflecting relatively strong capabilities (a high density) in products with relatively low potentials in income and diversification. Morocco’s peripheral position in the product space map matches its slow growth and points to the difficulty of diversification into more sophisticated products. Encouraging changes since 1990 include the development of a revealed comparative advantage for medium- and high-tech manufactures, which in 2010 represented around 40 percent of total goods exports. However, the number of goods involved is relatively small and this transformation has not sufficed to raise per capita growth to the average for middle-income countries. Export projections up to 2025 suggest that future developments will follow the trends of the past. Among sectors, high growth is likely for phosphate-based fertilizer exports. However, like edible oil products, which also may grow rapidly, phosphates are hampered by low income and diversification potentials. Along with various other manufactured products, electronics and the automotive industry are promising sectors that may offer more lasting positive contributions to Morocco’s future development. Beyond goods, Morocco’s policy makers should also consider the potential contributions of service exports, which in recent years have enjoyed rapid growth.